2003
DOI: 10.1128/jcm.41.12.5546-5550.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methodology for Serotyping Invasive and Nasopharyngeal Isolates of Haemophilus influenzae in the Ongoing Surveillance in Brazil

Abstract: To assess the magnitude of discrepant results obtained by routine Haemophilus influenzae serotyping, 258 isolates, collected by the epidemiological surveillance system in Brazil from individuals with invasive diseases or carriage, were evaluated by two slide agglutination (SlAg) methods: SlAg method 1, by which strains were initially screened with a serotype b-specific antiserum, and SlAg method 2, by which strains were tested against all serotype-specific antisera in parallel. Investigators comparing results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
3
12
0
1
Order By: Relevance
“…This result is in accordance with those reported by La Claire et al (7) and Bokerman et al (1). However, as previously reported (1), the use of all antisera in parallel (SAST 2), significantly improved capsule type agreement with PCR.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…This result is in accordance with those reported by La Claire et al (7) and Bokerman et al (1). However, as previously reported (1), the use of all antisera in parallel (SAST 2), significantly improved capsule type agreement with PCR.…”
supporting
confidence: 82%
“…The first PCR reaction detected the bexA gene responsible for the transport of capsular material; its presence or absence determines whether an isolate is encapsulated or nonencapsulated and therefore, nontypeable (NTHi). The second PCR assay using capsule type specific primers (a to f) is then used to determine the capsule types of the isolates (1,4,7). The aim of the present study was to verify the discrepancy between slide agglutination methods and the PCR method in the identification of the serotypes of Hi isolates from healthy carriers of the bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the specificity of case definition is low, when the actual incidence decreases, the predictive value of diagnostic tests also decreases, and the proportion of false-positive H. influenzae diagnoses increases. Fur-thermore, a recent study 2 of H. influenzae isolates obtained from different Brazilian regions showed discordant results between routine serotyping (latex agglutination) and the PCR technique, considered as the gold standard. The results of this study ratify the need for a reevaluation of the laboratory procedure protocols used in H. influenzae serotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that both the real-time and the gel-based PCR assays were more sensitive than the slide agglutination test for capsular typing of H. influenzae, as reported by others (1,6,13). Among our strains, 6% were Hib by real-time PCR, 5.4% were Hib by gel-based PCR, and 3% were Hib by serotyping.…”
mentioning
confidence: 55%